Potential for Powered Flight Neared by Most Close Avialan Relatives, but Few Crossed Its Thresholds - Pei, Rui (2020)
Uncertainties in the phylogeny of birds (Avialae) and their closest relatives have impeded deeper understanding of early theropod flight. To help address this, we produced an updated evolutionary hypothesis through an automated analysis of the Theropod Working Group (TWiG) coelurosaurian phylogenetic data matrix. Our larger, more resolved, and better-evaluated TWiG-based hypothesis supports the grouping of dromaeosaurids + troodontids (Deinonychosauria) as the sister taxon to birds (Paraves) and the recovery of Anchiornithinae as the earliest diverging birds. Although the phylogeny will continue developing, our current results provide a pertinent opportunity to evaluate what we know about early theropod flight. With our results and available data for vaned feathered pennaraptorans, we estimate the potential for powered flight among early birds and their closest relatives. We did this by using an ancestral state reconstruction analysis calculating maximum and minimum estimates of two proxies of powered flight potential—wing loading and specific lift. These results confirm powered flight potential in early birds but its rarity among the ancestors of the closest avialan relatives (select unenlagiine and microraptorine dromaeosaurids). For the first time, we find a broad range of these ancestors neared the wing loading and specific lift thresholds indicative of powered flight potential. This suggests there was greater experimentation with wing-assisted locomotion before theropod flight evolved than previously appreciated. This study adds invaluable support for multiple origins of powered flight potential in theropods (≥3 times), which we now know was from ancestors already nearing associated thresholds, and provides a framework for its further study. Video Abstract: [Figure presented] Pei et al. use an updated phylogeny of early birds and their closest relatives to reconstruct powered flight potential, showing it evolved at least three times. Many ancestors of the closest bird relatives neared thresholds of powered flight potential, suggesting broad experimentation with wing-assisted locomotion before theropod flight evolved.